Public administration the basics - Schiavo-Campo, Salvatore (Routledge, 2023)
There is a distinction between public policy ("what is to be done") and public administration ("how it is to be done"). The outcomes of government policies depend in large part on how policies are executed and who is responsible for their execution. Public administration is the set of instruments -- the rules, incentives, organizations, information, systems and people -- to implement public policy. Public Administration: The Basics is a reader-friendly and up-to-date synthesis of the subject, complete with relatable examples, analogies, and real-world illustrations.